"The Apostle of the Apostles," Prostitute or Penitent? A Typology of Mary Magdalene in the Homilies of Gregory the Great - Jóźwiak, Magdalena (Verbum Vitae, 2024)
Mary Magdalene, who is mentioned on the pages of the Gospels twelve times, is regarded as one of the most famous and stirring strong emotions women of the New Testament. In some religious circles to this day, one can still hear claims that Mary of Magdala was a prostitute. Others argue that Magdalene is the “Apostle of the Apostles” (Apostola Apostolorum) because she was the first person to bear witness to the risen Lord (e.g. Hippolytus of Rome, Jerome of Stridon). Pope Gregory the Great, on the other hand, combined three evangelical women into one figure in his two homilies: the nameless sinful woman (cf. Luke 7:37), Mary Magdalene (cf. Luke 8:2), and Mary mentioned in John 20:11 – into a single figure. Thus, Mary of Magdala was regarded as a prostitute. Gregory the Great’s theory became prevalent in Western Christianity over the next fifteen centuries. This paper aims to analyse homilies XXV and XXXIII by Gregory the Great and attempt to address the question of whether, for the popecommentator, Mary Magdalene is exclusively and mainly a symbol of the “convert prostitute?” This paper adopted the philological method. It concludes that perhaps the pope himself would have been astonished that for so many centuries, the most enduring legacy of his two aforementioned homilies is the image of Magdalene as a “convert prostitute” rather than the moral teaching he wanted to convey. After all, the commentator also juxtaposed Magdalene with the Shulamite from the Song of Songs, Eve, Simon the Pharisee, Peter, Zacchaeus and Dismas, and saw in her a “type” of a Christian of every era.